PENGARUH KEPUASAN PELANGGAN DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PT BATAMINDO EXECUTIVE VILLAGE - Febrinda, Febrinda; Syaifullah, Syaifullah (SCIENTIA JOURNAL, 2019)
This study aims to analyze the Influence Customer Satisfaction and Service Quality to Customer Loyalty PT Batamindo Executive Village. This study uses a quantitative approach. The population used is all customers of PT. Batamindo Executive Village as many as 2715 people by using judgment sampling technique samples obtained as many as 100 people. The results of this studi indicate that partially independent variabel that is castomer satisfaction has a positive and significant impact on castomer loyalty with the calculation results obtained tcount 0.7,779 > ttabel 1.98472 at the level of significance 0,000 < α 0.05 and quality service variables have a positive and significant on customer loyalty with the calculation results obtained tcount 3.562 > ttable 1.98472 at the level of significance 0.001 < α 0.05. Customer satisfaction and quality service simultaneously have a positive and significant effect on customer loyalty with the calculation result Fcount 91,770 > Ftable 3,03 with significance level 0,000 < α 0,05. The results of this study indicate that customer satisfaction and service quality influence on customer loyalty PT. Batamindo Executive Village.